THE EFFECT OF TEACHERS' PERCEPTIONS OF ORGANIZATIONAL JUSTICE ON ORGANIZATIONAL SILENCE - Vurkun, Meltem; Katitas, Sevda; Korumaz, Mithat (SCIENTIA SOCIALIS, 2025)
This study was conducted to determine the effect of teachers' perceptions of organizational justice on organizational silence. A causal-comparative and correlational survey model was used in the research. The sample of the study consisted of 446 teachers working in & Idot;stanbul, selected through simple random sampling. The research data were collected using the Organizational Justice Scale and the Organizational Silence Scale. Descriptive statistics, along with independent sample t-tests, correlation, and regression analyses, were employed to examine the collected data. As a result of the study, it was determined that teachers held moderate perceptions regarding organizational justice as well as organizational silence. The study revealed that teachers'perceptions of organizational justice differed according to gender and school type, while their perceptions of organizational silence differed according to subject branch. The findings indicated a significant negative correlation between organizational justice and organizational silence. Moreover, teachers'perceptions ofjustice within their institutions were found to be significant predictors of how they perceived organizational silence. This study underscores the decisive role of organizational justice in shaping teachers'silence behaviors. Implementing transparent, fair, and participatory practices in educational institutions can foster teachers' sense of value and empowerment, thereby enhancing organizational effectiveness and the overall quality of education. Such practices reduce silence while fostering communication, collaboration, and innovation among teachers.
Keywords: organizational justice; organizational silence; correlational survey model; teachers; EMPLOYEE SILENCE; MEDIATOR; CYNICISM; BEHAVIOR; VOICE; Education & Educational Research